2018
DOI: 10.1002/eat.22943
|View full text |Cite
|
Sign up to set email alerts
|

Prospective health associations of drive for muscularity in young adult males

Abstract: The drive for muscularity appears to be relatively prevalent across adolescence and early adulthood in males and is associated with broad and substantial health consequences. Muscularity-oriented concerns should be carefully considered when assessing and treating males with body image dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 49 publications
1
28
0
3
Order By: Relevance
“…The 7-item (3, 4, 10, 15, 16, 17, and 18) physical health domain includes questions about dependence on medicinal substances and medical aids, pain and discomfort, activities of daily living, energy and fatigue, mobility, sleep, and rest and work capacity. The 6-item (5,6,7,11,19, and 26) psychological health domain includes questions about self-esteem, body image and appearance, negative and positive feelings, spirituality-religion, personal beliefs, and concentration. The social relations domain assesses personal relationships, social support, and sexual activity; it comprises 3 items (from 20 to 22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 7-item (3, 4, 10, 15, 16, 17, and 18) physical health domain includes questions about dependence on medicinal substances and medical aids, pain and discomfort, activities of daily living, energy and fatigue, mobility, sleep, and rest and work capacity. The 6-item (5,6,7,11,19, and 26) psychological health domain includes questions about self-esteem, body image and appearance, negative and positive feelings, spirituality-religion, personal beliefs, and concentration. The social relations domain assesses personal relationships, social support, and sexual activity; it comprises 3 items (from 20 to 22).…”
Section: Methodsmentioning
confidence: 99%
“…However, the body image possessed by men is more complex compared to women, since men desire to achieve a muscular/athletic body along with low body fat [3]. These desires are associated with the drive for muscularity, which comprise muscle-gain -related attitudes and behaviors such as muscle-gain-related eating, excessive exercising, and dieting [5]. Studies in men have demonstrated that men's athletic/muscular and thin ideal internalizations are associated with the development of pathologic eating as well [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…adolescents; and instead have focused on the following areas: social and biological factors such as the media and peer pressure (4), internalization of athletic physique (19), weight concerns (1), and general somatic features (20). Therefore, investigating psychological factors can bridge this research gap.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐sectional studies have shown that muscularity concerns and disordered eating are associated with athletic participation given sport‐related pressures for weight and performance (Petrie, Greenleaf, Reel, & Carter, ; Thompson & Sherman, ), binge drinking and drug use (Calzo et al, ), and depression (Grossbard, Atkins, Geisner, & Larimer, ; Olivardia, Pope, Borowiecki, & Cohane, ). Adolescent males and young males with concerns about muscularity had higher odds of prospectively developing depressive symptoms, binge drinking, dieting, and use of muscle‐building products (Eik‐Nes, Austin, Blashill, Murray, & Calzo, ; Field et al, ). Adolescent predictors of thinness‐oriented disordered eating behaviors in young adulthood include depression, physical abuse, poor body image, and family, school, or community disconnectedness (Nagata, Garber, Tabler, Murray, & Bibbins‐Domingo, ).…”
Section: Introductionmentioning
confidence: 99%